Model E-Supsate untuk Pembelajaran yang Lebih Bermakna pada Program Studi Pendidikan IPS di Perguruan Tinggi Islam - Rahmad, Darmairal (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
This research aims to synthesize the Problem-Base Learning Model, Inquiry-Based Learning Model, and The Flipped Classroom Approach Model into a new learning model. The research method used is literature study. The number of articles relevant to the three learning models studied is 49 articles published in the last 10 years (2014-2024). The article is divided into three data groups, namely (1) Problem-Base Learning Model data group (D1), (2) Inquiry-Based Learning Model data group (D2), and (3) The Flipped Classroom Approach Model data group (D3). . These three groups of data are the result of stages (1) identifying literature, (2) studying literature, and (3) analyzing literature. The next stage is to synthesize D1, D2, and D3 into a learning model called the E-Supsate Model (Four Interconnected Viewpoints Model). This model is a learning model that connects every theoretical concept, theme, topic, social problem, social phenomenon or case to various social science disciplines and Islamic religious knowledge. These relationships have a common ground which is called the core of social reality meaning. Thus, this model produces a holistic learning experience in the form of (1) holistic understanding, (2) holistic internalization of Islamic values, and (3) holistic critical thinking.